2013
DOI: 10.1371/journal.pone.0076441
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Sponge Assemblages to Temperature Anomalies: Resilience and Proliferation of Sponges following the 1997–8 El-Niño Southern Oscillation

Abstract: Coral reefs across the world are under threat from a range of stressors, and while there has been considerable focus on the impacts of these stressors on corals, far less is known about their effect on other reef organisms. The 1997–8 El-Niño Southern Oscillation (ENSO) had notable and severe impacts on coral reefs worldwide, but not all reef organisms were negatively impacted by this large-scale event. Here we describe how the sponge fauna at Bahia, Brazil was influenced by the 1997–8 ENSO event. Sponge assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 65 publications
2
64
0
Order By: Relevance
“…Chondrilla nucula was mostly responsible for the increased abundance in response to more substrate becoming available through coral mortality. Increases in sponge abundance for an entire sponge assemblage following the same ENSO event were also reported in a 16‐year study (1995–2011) in Bahia, Brazil (Kelmo et al ), where the abundance of most subtidal benthic organisms declined dramatically and in some cases were extirpated. Although the abundance of many sponge species increased more than 10 times their initial densities by 2011, others showed decreased abundance.…”
Section: Resultssupporting
confidence: 73%
“…Chondrilla nucula was mostly responsible for the increased abundance in response to more substrate becoming available through coral mortality. Increases in sponge abundance for an entire sponge assemblage following the same ENSO event were also reported in a 16‐year study (1995–2011) in Bahia, Brazil (Kelmo et al ), where the abundance of most subtidal benthic organisms declined dramatically and in some cases were extirpated. Although the abundance of many sponge species increased more than 10 times their initial densities by 2011, others showed decreased abundance.…”
Section: Resultssupporting
confidence: 73%
“…For example, the growth and survival of several Carribean sponges remained unaffected by exposure to thermal stress [11]. Furthermore, the sponge assemblage in Bahia, Brazil, did not change between pre- and post-El Niño Southern Oscillation (ENSO) years [12]. In contrast, some studies have described the negative effects of elevated temperature on different sponge species.…”
Section: Introductionmentioning
confidence: 99%
“…While the potential impacts of climate-driven ocean changes are well documented for kelp (Wernberg et al 2010, Johnson et al 2011) and coral species (Spillman et al 2013), there remains uncertainty about how future climate change is likely to influence the distribution of non-coral benthic sessile invertebrates (Przeslawski et al 2008, Kelmo et al 2013. Recent studies have shown inconsistent results, with some indicating that under warmer future climate conditions, deep sessile organisms, particularly sponges, may benefit (e.g.…”
Section: Baseline To Monitor and Predict Future Climatedriven Changesmentioning
confidence: 99%
“…Recent studies have shown inconsistent results, with some indicating that under warmer future climate conditions, deep sessile organisms, particularly sponges, may benefit (e.g. colonise and establish on newly available reef space due to declines in other habitat-forming species, such as corals; Norström et al 2009, González-Rivero et al 2011, Kelmo et al 2013, while others suggest negative impacts (e.g. mass mortalities due to extreme climatic events such as marine heat waves; Cerrano et al 2000, Perez et al 2000, Garrabou et al 2009, Cebrian et al 2011).…”
Section: Baseline To Monitor and Predict Future Climatedriven Changesmentioning
confidence: 99%